Femtosecond harmonic mode-locking of a fiber laser at 3.27 GHz using a bulk-like, MoSe2-based saturable absorber - Koo, Joonhoi; Park, June; Lee, Junsu; Jhon, Young Min; Lee, Ju Han (OPTICAL SOC AMER, 2016)
We experimentally demonstrate the use of a bulk-like, MoSe2-based saturable absorber (SA) as a passive harmonic mode-locker for the production of femtosecond pulses from a fiber laser at a repetition rate of 3.27 GHz. By incorporating a bulk-like, MoSe2/PVA-composite-deposited side-polished fiber as an SA within an erbium-doped-fiber-ring cavity, mode-locked pulses with a temporal width of 737 fs to 798 fs can be readily obtained at various harmonic frequencies. The fundamental resonance frequency and the maximum harmonic-resonance frequency are 15.38 MHz and 3.27 GHz (212th harmonic), respectively. The temporal and spectral characteristics of the output pulses are systematically investigated as a function of the pump power. The output pulses exhibited Gaussian-temporal shapes irrespective of the harmonic order, and even when their spectra possessed hyperbolic-secant shapes. The saturable absorption and harmonic-mode-locking performance of our prepared SA are compared with those of previously demonstrated SAs that are based on other transition metal dichalcogenides (TMDs). To the best of the authors' knowledge, the repetition rate of 3.27 GHz is the highest frequency that has ever been demonstrated regarding the production of femtosecond pulses from a fiber laser that is based on SA-induced passive harmonic mode-locking. (C) 2016 Optical Society of America
Keywords: TRANSITION-METAL DICHALCOGENIDES; MOLYBDENUM DISELENIDE MOSE2; BLACK PHOSPHORUS; ALL-FIBER; PULSE GENERATION; DISULFIDE MOS2; ABSORPTION; YB; GRAPHENE; WS2